S + C + L Band tunable wavelength conversion using FWM dual-wavelength fiber laser in a highly nonlinear fiber - Awang, N.A.; Latif, A.A.; Zulkifli, M.Z.; Ghani, Z.A.; Harun, Sulaiman Wadi; Ahmad, Harith (John Wiley & Sons, 2013)
In this article, a novel wideband wavelength conversion is demonstrated using a highly nonlinear fiber consisting of a fluorine-doped fiber that has a high delta core and surrounded by a deeply depressed ring as opposed to the use of photonic crystal fibers.The wavelength conversion range is from 1460 to 1640 nm, which covers the S-, C- and L-bands of the optical network. The interacting waves consist of an arrayed waveguide grating tuned dual-wavelength fiber laser output together with a tunable laser source signal. A four-wave-mixing conversion of efficiency of −20 dB is achieved within a 70 nm tuning range within a 3.9 dB fluctuation. An optical signal to noise ratio of 30 dB is also realized within the same tuning range.